2022
DOI: 10.1108/lht-05-2022-0242
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical model and empirical analysis of university library readers' spatial cognition

Abstract: PurposeThe practice of renovation and construction of university libraries is flourishing, but how to attract readers to use the library is an issue that urgently needs to be explored. Spatial cognition is a subjective judgment of a person's tendency to take action in the future and implies behavioral intention. Based on the sensory–image–cognition relationship, a theoretical model of university library readers' spatial cognition is conducted, and the influencing factors and mechanisms of spatial cognition are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
(101 reference statements)
0
2
0
Order By: Relevance
“…Libraries are transforming from a space to store books into integrated cultural, meeting and learning spaces that tend to operate 24/7 (Yip et al , 2019; Chan et al , 2020a; Kim et al , 2020; Leung et al , 2022; Ho et al , 2022a,b; Jiang et al , 2022; Wong and Chiu, 2023). Noh (2022) investigated the library as a complex cultural space and showed that library users participated and enjoyed its services and programs.…”
Section: Transformation Of Librariesmentioning
confidence: 99%
“…Libraries are transforming from a space to store books into integrated cultural, meeting and learning spaces that tend to operate 24/7 (Yip et al , 2019; Chan et al , 2020a; Kim et al , 2020; Leung et al , 2022; Ho et al , 2022a,b; Jiang et al , 2022; Wong and Chiu, 2023). Noh (2022) investigated the library as a complex cultural space and showed that library users participated and enjoyed its services and programs.…”
Section: Transformation Of Librariesmentioning
confidence: 99%
“…One is that this paper adopts a literature review approach to analyze the spatial literacy of librarians by focusing on the trajectory of literature related to library space. However, not all librarians and practitioners document their experiences of space construction and spatial research ideas, so in order to be able to fully investigate librarians' space management competencies, an empirical investigation should also be conducted, and another study by the current research team is an empirical study of space services and management [87]. Secondly, our selection of literature was limited to peer-reviewed journals and dissertations.…”
Section: Limitations Of the Studymentioning
confidence: 99%